Gender Differences in the Path From Sexual Victimization to HIV Risk Behavior Among Homeless Youth. Issue 3 (3rd April 2017) - Harris, Taylor; Rice, Eric; Rhoades, Harmony; Winetrobe, Hailey; Wenzel, Suzanne
ABSTRACT: Experiencing sexual victimization prior to becoming homeless is common among homeless youth and is associated with increased HIV risk behavior. This study examined mediating variables that underlie this association, adding to the understanding of gender differences in these paths. Participants were homeless youth in Los Angeles recruited through service access centers who completed a computerized self-administered interview in English or Spanish using an iPad. Findings indicate a high presence of sexual victimization across both genders. Female participants experienced posttraumatic stress disorder and subsequent engagement with exchange sex, whereas male participants were primarily involved in substance use risk pathways. Results indicate paths in the association between sexual victimization and HIV risk behavior differ between male and female homeless youth. Gender-specific, mental-health-informed interventions targeting sexual risk reduction are warranted.